Activating FLT3 Mutants Show Distinct Gain-of-Function Phenotypes In Vitro and a Characteristic Signaling Pathway Profile Associated with Prognosis in Acute Myeloid Leukemia - Janke, Hanna (Public Library of Science, 2014)
About 30% of patients with acute myeloid leukemia (AML) harbour mutations of the receptor tyrosine kinase FLT3, mostly internal tandem duplications (ITD) and point mutations of the second tyrosine kinase domain (TKD). It was the aim of this study to comprehensively analyze clinical and functional properties of various FLT3 mutants. In 672 normal karyotype AML patients FLT3-ITD, but not FLT3-TKD mutations were associated with a worse relapse free and overall survival in multivariate analysis. In paired diagnosis-relapse samples FLT3-ITD showed higher stability (70%) compared to FLT3-TKD (30%). In vitro, FLT3-ITD induced a strong activating phenotype in Ba/F3 cells. In contrast, FLT3-TKD mutations and other point mutations – including two novel mutations – showed a weaker but clear gain-of-function phenotype with gradual increase in proliferation and protection from apoptosis. The pro-proliferative capacity of the investigated FLT3 mutants was associated with cell surface expression and tyrosine 591 phosphorylation of the FLT3 receptor. Western blot experiments revealed STAT5 activation only in FLT3-ITD positive cell lines, in contrast to FLT3-non-ITD mutants, which displayed an enhanced signal of AKT and MAPK activation. Gene expression analysis revealed distinct difference between FLT3-ITD and FLT3-TKD for STAT5 target gene expression as well as deregulation of SOCS2, ENPP2, PRUNE2 and ART3. FLT3-ITD and FLT3 point mutations show a gain-of-function phenotype with distinct signalling properties in vitro. Although poor prognosis in AML is only associated with FLT3-ITD, all activating FLT3 mutations can contribute to leukemogenesis and are thus potential targets for therapeutic interventions.